Ocena pravilnosti in primernosti antibiotičnega predpisovanja pri odraslih bolnikih z bakterijskimi okužbami - Rupnik, Barbara (Medicinski razgledi, 2008)
BACKGROUND: Inappropriate use of antibiotics is linked to the emergence and dissemination of antimicrobial-resistant bacteria. Guidelines for antimicrobial prescribing are a possible intervention to increase the appropriateness of antimicrobial prescribing. AIMČ To measure the influence ofthe Guidelines for antimicrobial prescribing published in 2006, compared to those published in 1998 concerning the appropriateness and correctness of antibiotic use. To find out whether there is a statistically significant difference in the impact of the two guidelines on antimicrobial prescribing. To establish the most common mistakes arising in connection to antimicrobial prescribing. HYPOTHESIS: The guidelines published in 2006 increased the appropriateness and correctness of antimicrobial prescribing. The choice of the appropriate antibiotic and the duration of therapy are the most common mistakes associated with antimicrobial prescribing. METHODS: The study included 100 subsequent adult patients from the Department of Infectious Diseases in Ljubljana who were hospitalized in November 2005, and 100 subsequent adult patients hospitalized in November 2006. The data was gathered by revising the patient charts. The study was retrospective and followed the established methodology of the appropriateness and correctness ofantimicrobial prescribing. RESULTSČ In 2006, 51.9% of antibiotic prescriptions were completely in line with the guidelines and in 2005 there were 35.3% such antibiotic prescriptions. In 4.7% (2006) and 6.4% (2005) of the cases, the antibiotic was prescribed without the appropriate indication. There was an increase in prescribing the first choice antibiotic and a decrease in incorrectly prescribed antibiotics in 2006. In 2005, incorrect duration of therapy was the most common mistake (22.0%), while in 2006 it was dosing (17.6%). The percentages of correctly documented antibiotic therapy in the two years were similar. (Abstract truncated at 2000 characters)
Keywords: Bacterial Infections; Zdravilo, uporaba; Bakterijske infekcije; Drug Therapy; antibiotic; Antibiotics; Antibiotiki; Drug Utilization; Hospitalizacija; Hospitalization; Odrasli; drug; Adult; zdravila; predpisovanje zdravil